Literacy and Learning : Reflections on Writing, Reading, and Society - Brandt, Deborah, 1951- (San Francisco Jossey-Bass, 2009)
Deborah Brandt has dedicated her career to the state of reading and writing in the United States, and her research on literacy and learning is well known and widely studied. This book, sponsored by the Grawemeyer Foundation, showcases her biggest ideas and contributions to the field, and includes a new introduction by Dr.
Include Index
Keywords: United States -- Language arts -- Literacy